The Impact of Human Resources Capacity and Policy on Disaster Preparedness: (Study at the Luwu Regency Regional Disaster Management Agency) - Zainal Efendy; S. Salju; Muchtar Surullah; S. Sapar (Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to describe and determine the effect of human resource capacity, policy, and disaster preparedness. This study uses a quantitative method by taking a sample of 80 respondents from the Luwu Regency Regional Disaster Management Agency using the Slovin formula. Sources of data were obtained using questionnaires and interviews. The data collected was analyzed by Structural Equation Modeling (SEM) using the Smart PLS application. The results of the study show that Human Resource Capacity has an effect on disaster preparedness by 0.260 units with a t-count value = 4.129 > t table = 1.900 and a P-value = 0.000 <0.05. Policies have an effect on disaster preparedness by 0.737 units with a t-count value = 12,183 > t table = 1.900 and a P-value = 0.000 <0.05. The joint influence of Human Resource Capacity and Policy on disaster preparedness is 96.5 percent, while 3.5 percent is influenced by other variables not observed in this study.